Implementasi nilai Pancasila sila persatuan Indonesia masa pembelajaran daring peserta didik kelas V sekolah dasar - Eka Saputri, Chorin Luthfa; Mahfud, Hasan; Matsuri, Matsuri (Universitas Sebelas Maret, 2022)
This research aims to determine the implementation of the Pancasila values of Indonesian Unity in the Online Learning Period of fifth grade elementary school students.This research method uses qualitative research. The primary data from this research are the results of interviews with students who are the subject, the parents of students who are the subject and the fifth grade teacher of SD Negeri 2 Wonogondo. While secondary data is in the form of photo documentation during research and online learning observations. Data collection techniques used are observation, interviews and documentation. Test the validity of the data using triangulation techniques and sources. The data analysis technique used is the Miles and Huberman technique.The results of this study indicate that the implementation of the Pancasila values of the Indonesian Unity precepts at SD Negeri 2 Wonogondo is in the good category, but there are still 33% of students who only meet two of the four descriptors on the togetherness indicator. The indicators of love for the homeland and nation and respect for differences are in the good category, but the indicators of togetherness are in the medium category